1974
DOI: 10.1007/bf00388396
|View full text |Cite
|
Sign up to set email alerts
|

The role of nuclear fusion in pollen embryogenesis of Datura innoxia Mill.

Abstract: If anthers of Datura innoxia containing microspores are cultured at 28° C for 24 h, two forms of haploid pollen grains are produced; one with typical unequal generative and vegetative nuclei (A), and the other with equal vegetativetype nuclei (B). The A form predominates. After 24 to 72 h in culture, three embryogenic events ensue; 1) division of the vegetative cell in A grains accompanied by rapid degeneration of the generative cell, 2) simultaneous or independent mitosis of the nuclei in B grains, and 3) sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 13 publications
3
39
0
2
Order By: Relevance
“…4e and 4f). Similar pictures were presented by Sunderland et al (1974) and Chen et al (1984). Spontaneous chromosome duplication in microspore or anther culture was reported for many species.…”
Section: Chromosome Doublingsupporting
confidence: 81%
“…4e and 4f). Similar pictures were presented by Sunderland et al (1974) and Chen et al (1984). Spontaneous chromosome duplication in microspore or anther culture was reported for many species.…”
Section: Chromosome Doublingsupporting
confidence: 81%
“…C-mitosis, such as occurs during colchicine treatment, may result in a simple restitution nucleus with a doubled chromosome number. In Datura, it was proposed that both endoreduplication and nuclear fusion were involved in chromosome doubling and that the combination of both methods could explain the ploidy levels obtained, which were higher than diploid (Sunderland, 1974;Sunderland et al, 1974;Seguí-Simarro and Nuez, 2008). Nuclear fusion was described as occurring when two nuclei synchronously entered into division, formed a common metaphase plate and spindle and resulted in two nuclei, each with more than one set of chromosomes (Sunderland, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Anther culture has been already engaged for the production of androgenic haploids (Germanà et al 2005). Sunderland et al (1974) demonstrated the origin of triploids and tetraploids from anther culture. Single nucleus of an embryogenic grain divides asymmetrically into a generative and a vegetative nucleus.…”
Section: Introductionmentioning
confidence: 99%